SUMOylation mediates CtIP’s functions in DNA end resection and replication fork protection - Locke, Andrew J (Nucleic Acids Res, 2021)
Double-strand breaks and stalled replication forks are a significant threat to genomic stability that can lead to chromosomal rearrangements or cell death. The protein CtIP promotes DNA end resection, an early step in homologous recombination repair, and has been found to protect perturbed forks from excessive nucleolytic degradation. However, it remains unknown how CtIP’s function in fork protection is regulated. Here, we show that CtIP recruitment to sites of DNA damage and replication stress is impaired upon global inhibition of SUMOylation. We demonstrate that CtIP is a target for modification by SUMO-2 and that this occurs constitutively during S phase. The modification is dependent on the activities of cyclin-dependent kinases and the PI-3-kinase-related kinase ATR on CtIP’s carboxyl-terminal region, an interaction with the replication factor PCNA, and the E3 SUMO ligase PIAS4. We also identify residue K578 as a key residue that contributes to CtIP SUMOylation. Functionally, a CtIP mutant where K578 is substituted with a non-SUMOylatable arginine residue is defective in promoting DNA end resection, homologous recombination, and in protecting stalled replication forks from excessive nucleolytic degradation. Our results shed further light on the tightly coordinated regulation of CtIP by SUMOylation in the maintenance of genome stability.